(untitled) (Research, Society and Development, 2021)
The objective was to correlate nutritional status with gastrointestinal symptoms in adolescents from a capital city in northeastern Brazil. This is a cross-sectional study with a descriptive and analytical approach in Fortaleza / CE, which occurredin the first semester of 2017 with 199 students from public and private schools aged 11 to 19 years old, attending the 6th to 9th grade. The results showed that 66.8% were up to 14 years old, 58.8% were female and 53.3% came from a public school. 46.7% of the adolescents were overweight, and 75.4% had adequate waist circumference (WC). Although most of them have a satisfactory waist size, the waist-to-height ratio (RCE) was high in 59.8% of the students. 35.2% of the adolescents reported feeling always or almost always some gastrointestinal symptom, of which the most frequent were: (12.6%) gas, (12.1%) abdominal distension, (11.6%) constipation and (10.1%) pain. There was a significant relationship between nutritional status and the type of school attended, as well as between WC and RCE with overweight. The female sex has a higher risk of presenting symptoms when compared to the male sex. Adolescents with elevated WC are more at risk of developing gastrointestinal symptoms. The association between symptoms and other variables was only found with sex in the adjusted model. In view of the results, there is a need for early detection of risk factors and changes in lifestyle, especially for females, which is strongly associated with the presence of gastrointestinal symptoms. Nutritional status was not associated with the presence of gastrointestinal symptoms.